Pancreatic Fluid Interleukin-1β Complements Prostaglandin E2 and Serum Carbohydrate Antigen 19-9 in Prediction of Intraductal Papillary Mucinous Neoplasm Dysplasia. Issue 8 (September 2019) - Simpson, Rachel E.; Yip-Schneider, Michele T.; Flick, Katelyn F.; Wu, Huangbing; Colgate, Cameron L.; Schmidt, C. Max
Abstract : Objectives: We sought to determine if interleukin (IL)-1β and prostaglandin E2 (PGE2) (inflammatory mediators in pancreatic fluid) together with serum carbohydrate antigen (CA) 19-9 could better predict intraductal papillary mucinous neoplasm (IPMN) dysplasia than individual biomarkers alone. Methods: Pancreatic cyst fluid (n = 92) collected via endoscopy or surgery (2003–2016) was analyzed for PGE2 and IL-1β (enzyme-linked immunosorbent assay). Patients had surgical pathology-proven IPMN. Threshold values (PGE2 [>1100 pg/mL], IL-1β [>20 pg/mL], and serum CA 19-9 [>36 U/mL]) were determined. Results: Levels of IL-1β were higher in high-grade dysplasia (HGD)/invasive-IPMN (n = 42) compared with low/moderate IPMN (n = 37) (median [range], 54.6 [0–2671] vs 5.9 [0–797] pg/mL; P < 0.001; area under curve [AUC], 0.766). Similarly, PGE2 was higher in HGD/invasive IPMN (n = 45) compared with low/moderate IPMN (n = 47) (median [range], 1790 [20–15, 180] vs. 140 [10–14, 630] pg/mL; P < 0.001; AUC, 0.748). Presence of elevated PGE2 and IL-1β (AUC, 0.789) provided 89% specificity and 82% positive predictive value (PPV) for HGD/invasive IPMN. Elevated levels of all 3 provided 100% specificity and PPV for HGD/invasive IPMN. Conclusions: Cyst fluid PGE2, IL-1β, and serum CA 19-9 in combination optimize specificity and PPV for HGD/invasive IPMN and may help build a panel of markers to predict IPMN dysplasia.